ChemInform Abstract: Photoredox Catalysis for the Generation of Carbon Centered Radicals. Issue 47 (3rd November 2016) - Goddard, Jean‐Philippe; Ollivier, Cyril; Fensterbank, Louis
Abstract: Review: 83 refs.